An overview of Leishmaniasis with a focus on the island of Cyprus - Kerkuklu, Namik Refik; Guran, Mumtaz (Wolters Kluwer Medknow Publications, 2020)
Leishmaniasis is a parasitic disease of tropics, subtropics, and southern Europe which is classified as a neglected tropical disease. There is a paucity of knowledge for this disease especially in some parts of the world where leishmaniasis is endemic such as Cyprus island in the Mediterranean. This narrative review revealed cutaneous leishmaniasis (CL) and visceral leishmaniasis (VL) as the dominant type of human leishmaniasis in the island. Host and disease type identification studies based on cats, dogs and rats showed Leishmania infantum parasite to be the leading species among others with a seroprevalence rate ranging from 3.55% to 14.9% in selected hosts with an indication of dogs as the main animal reservoir. Lack of focus on potential wild animal hosts creates an important evidence gap to overcome for the purpose of controlling leishmaniasis. We aim to present asynoptical review of leishmaniasis to critically analyse currently available data in literature about this disease in Cyprus.
Keywords: Leishmaniasis; Kala azar; vector borne diseases; Cyprus